2010
DOI: 10.1097/qai.0b013e3181bf1c45
|View full text |Cite
|
Sign up to set email alerts
|

Undiagnosed HIV Prevalence Among Adults and Adolescents in the United States at the End of 2006

Abstract: Differences in undiagnosed HIV were evident across demographic and behavior groups. Effective testing programs and early access to treatment and prevention services are necessary to reduce undiagnosed HIV infections and HIV prevalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
129
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 200 publications
(133 citation statements)
references
References 25 publications
3
129
0
1
Order By: Relevance
“…18 A 2008 study that included multiple partner-level factors found that having a partner with an unknown HIV status was associated with HIV and was more commonly reported by black than white MSM. 19 Furthermore, black men are estimated to have the highest number of unidentified HIV infections, 20 and studies have found that minority MSM (black, Hispanic, mixed race) were more likely to be unaware of their HIV infection. [21][22][23] Additionally, access to antiretroviral therapy which has been associated with reduced HIV transmission 24 is lower among black MSM.…”
Section: Resultsmentioning
confidence: 99%
“…18 A 2008 study that included multiple partner-level factors found that having a partner with an unknown HIV status was associated with HIV and was more commonly reported by black than white MSM. 19 Furthermore, black men are estimated to have the highest number of unidentified HIV infections, 20 and studies have found that minority MSM (black, Hispanic, mixed race) were more likely to be unaware of their HIV infection. [21][22][23] Additionally, access to antiretroviral therapy which has been associated with reduced HIV transmission 24 is lower among black MSM.…”
Section: Resultsmentioning
confidence: 99%
“…It is important to note that rates in our study approximate the self-report rates of known HIV infection in the NHBS sample. Although the GRINDR sample did not acquire any biologic specimens for HIV or STI testing, self-reports of HIV-positive serostatus almost universally underestimate the true seroprevalence rate 16 attributable primarily to occult and undiagnosed HIV infection and secondarily to the persistent stigma associated with reporting an HIVpositive diagnosis among MSM. 17 Participants demonstrated a high rate of ongoing transmission-associated risk behavior, indicating that the sample is an excellent target for recruitment for and ultimate deployment of HIV prevention studies and interventions, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…6 But overall adoption of routine HIV testing remains low 7 and it is estimated that 21% of people living with HIV still remain undiagnosed. 8 Although an additional 11 million Americans have been tested since 2006, approximately 100 million adolescents and adults are unaware of their HIV status.…”
Section: Introductionmentioning
confidence: 99%